2014
DOI: 10.1021/ie502150g
|View full text |Cite
|
Sign up to set email alerts
|

Novel Coconut Oil Based Magnetite Nanofluid as an Ecofriendly Oil Spill Remover

Abstract: The removal of oil spills from a water surface has huge industrial importance, in view of ecological safety. A novel, ecofriendly coconut oil based magnetite nanofluid is prepared by the coprecipitation method, for removing oil contaminants from water. Magnetic particles with face centered cubic crystal structure and superparamagnetic behavior are prepared and used to get a stable suspension in coconut oil. The superhydrophobicity and superoleophilicity of the nanofluid are examined through contact angle measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 30 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Two main factors influence the sorption capacity of ZIFs; namely, their hydrophobicity and their specific surface area Nabeel Rashin et al, 2014). Wettability is assessed by the water contact angle (WCA).…”
Section: Sorptionmentioning
confidence: 99%
“…Two main factors influence the sorption capacity of ZIFs; namely, their hydrophobicity and their specific surface area Nabeel Rashin et al, 2014). Wettability is assessed by the water contact angle (WCA).…”
Section: Sorptionmentioning
confidence: 99%
“…Compared with other magnetic composite materials, MRFs are ecofriendly materials and show good oil removal performance. Rashin et al 21 removed oil slick (motor oil) with the coconut oil-based MRF, and the oil removal efficiency was 91%. But coconut oil can cause secondary pollution and affect the reuse of oil slick.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other magnetic composite materials, MRFs are ecofriendly materials and show good oil removal performance. Rashin et al 21 secondary pollution, Tian et al 22 used the lubricant oil-based MRF for removing oil slick (lubricant oil), and the efficiency of the lubricant oil-based MRF exceeds by 90%. However, these oil removal experiments of MRF are carried out on a fresh water surface, and the influence of water salinity was not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…16 Regarding hydrophobicity, in some cases the usage of surfactants or grafting polymers around magnetic nanoparticles is needed to introduce oleophilic characteristics to their surface. 17 Furthermore, using other magnetic nanomaterial has been also reported for oil spill cleanup, such as graphene aerogel/Fe 3 O 4 / polystyrene composites, 18 magnetic macroporous carbon nanotubes (CNT), 19 and magnetic graphene foam. 20 They showed an outstanding performance in oil spill removal and strong recyclability with oil removal capacities of 40, 56, and 28 g/g, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Their effectiveness is limited by two main factors: the specific surface area and particles hydrophobicity. , Previous studies about magnetic iron oxide nanoparticles have reported specific surface areas around 96 m 2 /g . Regarding hydrophobicity, in some cases the usage of surfactants or grafting polymers around magnetic nanoparticles is needed to introduce oleophilic characteristics to their surface . Furthermore, using other magnetic nanomaterial has been also reported for oil spill cleanup, such as graphene aerogel/Fe 3 O 4 / polystyrene composites, magnetic macroporous carbon nanotubes (CNT), and magnetic graphene foam …”
Section: Introductionmentioning
confidence: 99%